1985
DOI: 10.1007/bf00257530
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of adrenal suppression by high-dose medroxyprogesterone acetate in breast cancer patients

Abstract: To investigate the mechanism of adrenal suppression by high-dose MPA, we performed direct and indirect stimulation tests in postmenopausal women with disseminated breast cancer who were receiving MPA and in a postmenopausal breast cancer control group. A partial adrenal insufficiency was found during Synacthen stimulation, confirmed by a slight increase of 11-desoxycortisol after metyrapone, despite a sufficient rise in ACTH levels. Peak levels of androstenedione and 17-OH progesterone after Synacthen correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Therefore, the antitumoral effects of high-dose MPA might be less derived from the progesterone receptor cascades than from cytotoxic effects on the tumor cell (12). Increased oxidative activity of 17b-hydroxysteroid dehydrogenase (25) inducing the conversion of estradiol to estrone (26), suppression of adrenal androgen synthesis and reduction in estrogens as the metabolites of the peripheral conversion (27,28), or inhibition of angiogenesis (29,30) might be relevant. The effect of MPA on intracellular SHBG could be another mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the antitumoral effects of high-dose MPA might be less derived from the progesterone receptor cascades than from cytotoxic effects on the tumor cell (12). Increased oxidative activity of 17b-hydroxysteroid dehydrogenase (25) inducing the conversion of estradiol to estrone (26), suppression of adrenal androgen synthesis and reduction in estrogens as the metabolites of the peripheral conversion (27,28), or inhibition of angiogenesis (29,30) might be relevant. The effect of MPA on intracellular SHBG could be another mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that in postmenopausal women MPA may exert at least part of its activity by suppression of adrenal androgen synthesis and the consequent reduction in circulating oestrogens which are derived from the peripheral conversion of these androgens (van Veelen et al, 1985a, b). The further suggestion has been made that this inhibition of adrenal steroidogenesis may explain the higher response rate found during the use of high dose progestins (van Veelen et al, 1985a).…”
Section: Discussionmentioning
confidence: 99%
“…which induces an inhibition of the pituitary secretion of LH and FSH [3] and consequently a block on ovarian estrogen section. Furthermore MAP reduces also the peripheral conversion of androgens in es trogens [13], suppressing adrenal androgen secretion by a block of ACTH pituitary secretion. As a conse quence MAP induces an extensive and general es trogen suppression and it could therefore be suggested in the treatment of advanced breast cancer both in premenopausal and postmenopausal patients.…”
Section: Discussionmentioning
confidence: 99%